ApoB/ApoA‐I Ratio is Associated With Faster Hemodynamic Progression of Aortic Stenosis: Results From the PROGRESSA (Metabolic Determinants of the Progression of Aortic Stenosis) Study. Issue 4 (10th February 2018) - Tastet, Lionel; Capoulade, Romain; Shen, Mylène; Clavel, Marie‐Annick; Côté, Nancy; Mathieu, Patrick; Arsenault, Marie; Bédard, Élisabeth; Tremblay, Alexe; Samson, Marilie; Bossé, Yohan; Dumesnil, Jean G.; et al.
Abstract : Background: Previous studies reported that middle‐aged patients with atherogenic lipoprotein‐lipid profile exhibit faster progression of aortic valve stenosis (AS). The ratio of apolipoprotein B/apolipoprotein A‐I (apoB/apoA‐I) reflects the balance between atherogenic and anti‐atherogenic lipoproteins. The aim of this study was to examine the association between apoB/apoA‐I ratio and AS hemodynamic progression and to determine whether this association varies according to age. Methods and Results: A total of 159 patients (66±13 years, 73% men) with AS were prospectively recruited in the PROGRESSA (Metabolic Determinants of the Progression of Aortic Stenosis) study. Hemodynamic progression of AS was determined by the change in peak aortic jet velocity (Vpeak ) measured by Doppler‐echocardiography between baseline and 2‐year follow‐up. Patients in the top tertile of apoB/apoA‐I ratio (≥0.62) had a faster progression rate of AS compared with those in the bottom/mid tertiles (Vpeak progression: 0.30 [0.09˗0.49] versus 0.16 [0.01˗0.36] m/s, P =0.02). There was a significant interaction ( P =0.007) between apoB/apoA‐I ratio and age. Among younger patients (ie, aged <70 years; median value of the cohort), those in the top tertile of apoB/apoA‐I ratio had a 3.4‐fold faster AS progression compared with those in the bottom/mid tertiles (Vpeak progression: 0.34 [0.13˗0.69] versus 0.10 [−0.03˗0.31] m/s, P =0.002), whereas there was no significant difference between tertiles in the subgroup of older patients ( P =0.83). After comprehensive adjustment, higher apoB/apoA‐I ratio was significantly associated with faster AS progression in the subset of younger patients (all, standardized β≥0.36; P ≤0.01). Conclusions: Higher apoB/apoA‐I ratio is significantly associated with faster hemodynamic progression of AS in the younger patients. These findings suggest that atherogenic lipid factors may play a crucial role in the pathogenesis of AS in younger patients, but may be are less important in older patients. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01679431.